Efek Penambahan Vitamin C terhadap Aktivitas Klindamisin dalam Menghambat Pertumbuhan Streptococcus pneumoniae secara In Vitro - Bagus Dwi Kurniawan; Dini Agustina; Erfan Efendi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Pneumonia is one of the lower respiratory tract infection involving respiratory bronchioles and alveoli that mostly caused by Streptococcus pneumoniae.Clindamycin is one of the drug of choice for pneumoniae. This drugs inhibits the growth of S. pneumoniae by producing ROS (Reactive Oxygen Species). Recent study has shown that vitamin C could generate ROS leading to DNA-damage on bacteria. The aims of this study was to know the possible benefit effect of adding vitamin C towards clindamycin inhibition activity against the growth of S. pneumoniae in vitro. This research was conducted by using 7 groups which consist of negative control (aquades), positive control (clindamycin), and test group 1 until 5 that given the combination of clindamycin and vitamin C as follows 2,5 mg/ml; 5 mg/ml; 10 mg/ml; 20 mg/ml; and 40 mg/ml. The inhibition effect of growing S. pneumoniae shown by the inhibition zone diameter. The average of inhibition zone on negative control, positive control, and test group were 5; 24,12; 24,62; 26,08; 27,58; 28,74; and 29,76 mm. These result show a significant correlation based on Pearson test (the coefficient correlation’s result is +0,910). The logarithmic regression revealed the minimal concentration of vitamin C was 1,767 mg/ml. It can be concluded that vitamin C increased the activity of clindamycin by inhibiting the growth of S.pneumoniae in vitro. Keywords: Streptococcus pneumoniae, ROS, Clindamycin, Vitamin C